Study on the current situation and spatial distribution of intimate partner violence among Chinese residents - Zhang, Ruofan; Qu, Ge; Sun, Yuchao; Feng, Jing; Lei, Zihui; Li, Xinyan; Shen, Aoqi; Zuo, Yanli; Gan, Yong (Frontiers in Public Health, 2025)
BackgroundIntimate partner violence (IPV), defined as any behavior within an intimate relationship that causes physical, psychological, or sexual harm to those in the relationship, is a significant public health issue worldwide. To analyze the current status and spatial distribution patterns of IPV among residents in China, and identify the nationwide prevalence trends and regions of high severity, so as to provide a scientific basis for the formulation and implementation of government interventions.MethodsA multi-stage sampling approach was employed to conduct a psychological and behavioral survey among 31,449 residents in 148 cities across the nation from June to August 2022. IPV was measured using a self-developed scale that was specifically designed and culturally adapted for the Chinese context, and it was been categorized into psychological violence, physical violence and sexual violence. Geographic information system (GIS) technology and spatial analysis methods was applied. GeoDa 1.18, ArcGIS 10.8 and STATA 17 software were utilized for data analysis.ResultsThe prevalence rates of IPV among Chinese residents was 45.80%, and the prevalence rates of psychological violence, physical violence and sexual violence was 44.50, 21.65 and 18.96%, respectively. The standard deviation plot of prevalence rates across provinces revealed that residents in Shanghai consistently had higher rates of all three categories of IPV compared to the national average level. The results of local spatial auto-correlation analysis indicated that there was a high-high clustering pattern of overall prevalence rates of IPV in Jiangxi and Zhejiang provinces, and a high-low clustering pattern was observed in Jilin, Hebei, and Ningxia provinces. The distribution pattern of intimate partner psychological violence prevalence rates showed a similar clustering pattern as the overall IPV. Additionally, there was a low-low clustering pattern of intimate partner physical violence in Anhui province, and a low-low clustering pattern of intimate partner sexual violence was identified in Anhui and Shandong provinces.ConclusionThe prevalence rates of IPV in China was relatively high, especially in Shanghai, and there was a certain degree of spatial distribution difference, which urgently needs to be paid attention to by relevant departments and institutions, especially around Zhejiang and Jiangxi in eastern China.